Chia seed-mediated fabrication of ZnO/Ag/Ag2O nanocomposites: structural, antioxidant, anticancer, and wound healing studies - Rafique, Aisha; Amjad, Fatima; Janjua, Muhammad Ramzan Saeed Ashraf; Naqvi, Syed Ali Raza; Hassan, Sadaf Ul; Abdullah, Hanzla; Nazir, Muhammad Shahid; Ali, Zulfiqar; Alshihri, Abdulaziz A.; Momenah, Maha Abdullah; Mansour, Adel Abo; Bajaber, Majed A.; et al. (Frontiers in Chemistry, 2024)
Plant extract-mediated fabrication of metal nanocomposites is used in cell proliferation inhibition and topical wound treatment, demonstrating significant effectiveness. Salvia hispanica L. (chia) seed extract (CE) is used as the reaction medium for the green fabrication of ecofriendly ZnO(CE) nanoparticles (NPs) and Ag/Ag2O(CE) and ZnO/Ag/Ag2O(CE) nanocomposites. The resultant nanoparticles and nanocomposite materials were characterized using UV–visible, Fourier-transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD), and energy-dispersive X-ray (EDX) techniques. In the context of antioxidant studies, ZnO/Ag/Ag2O(CE) exhibited 57% reducing power and 86% 2,2, diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging. All three materials showed strong antibacterial activity against Staphylococcus aureus (S. aureus), Escherichia coli (E.coli), and Bacillus subtilis (B. subtilis) bacterial strains. Additionally, ZnO(CE), Ag/Ag2O(CE), and ZnO/Ag/Ag2O(CE) also revealed 64.47%, 42.56%, and 75.27% in vitro Michigan Cancer Foundation-7 (MCF7) cancer cell line inhibition, respectively, at a concentration of 100 μg/mL. Selectively, the most effective composite material, ZnO/Ag/Ag2O(CE), was used to evaluate in vivo wound healing potential in rat models. The study revealed 96% wound closure in 10 days, which was quite rapid healing compared to wound healing using clinically available ointment. Therefore, in conclusion, the ZnO/Ag/Ag2O(CE) nanocomposite material could be considered for further testing and formulation as a good anticancer and wound healing agent.